Maximum strength, relative strength, and strength deficit: relationships with performance and differences between elite sprinters and rrofessional rugby union players - Loturco, I.; Pereira, L. A.; Freitas, T. T.; Bishop, C.; Pareja-Blanco, F.; McGuigan, M. R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To test the relationships between maximum and relative strength (MS and RS), absolute and relative peak force (PF and RPF), and strength deficit (SDef), with sprint and jump performance, and to compare these mechanical variables between elite sprinters and professional rugby union players.